In silicostructural data analysis tothe impact of leu27pro and asp49gly mutations on pza resistance in mycobacterium tuberculosis - M.MUTHURAJ; V.LAKSHMI; C.K.VIDYA RAJ; S.ANBAZHAGI; B.USHARANI (International Journal of Pharma and Bio Sciences, 2016)
This study reports on the structural and functional basis of pyrazinamide (PZA) resistance conferred by the mutations Leu27Pro and Asp49Gly in pncA gene as sequenced from a PZA resistant Mycobacterium tuberculosis strain. Molecular modelling studies of Wild Type (WT) and Mutant Types (MT1, MT2) of Pyrazinamidase (PZase) showed the mutation at Leu27Pro and Asp49Gly do not impact on the conformation of the protein. However, comparing all the docking score, energy and interaction pattern with wild type Pzase, the M1 Pzase has no significance influence of mutant residues Leu27Pro which is reside in the N-terminal helices α3. But in case of M2 (Asp49Gly) mutant Pzase, the Asp49Gly is the prime residues for their active functionality by forming coordination interaction with Fe2+ is lost due to the mutation, which subsequently effects in their binding energy and docking score of -25.533 kcal/mol and -5.093 respectively. Moreover, the orientation of the PZA molecules was shifted of about 2.06 Å with respect to C3 atom and moved apart from its interaction with Ala102 instead it forms a hydrogen bond between D8 OD1 and N3 by contact distance of 2.667. Though, other interaction was retained, the less efficiency nature of coordination interaction and proper interaction pattern of PZA with Pzase makes M2 mutant shown efficacy less interaction nature and which indirectly lead for the resistant against PZA.